Benin : Poverty Reduction Strategy Paper-Annual Progress Report. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This paper reviews the Annual Progress Report (APR) on Poverty Reduction Strategy Paper (PRSP) on Benin. The APR presents an overview of the implementation of the strategy addressing in turn the new vision of development in Benin, the major projects initiated for the creation of national wealth and the situation of poverty, and the achievement of the Millennium Development Goals in Benin. The APR also focuses on the level of implementation of the strategy, and deals with the monitoring of the macroeconomic and budgeting framework.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet